The Efficacies of Heritage: Syndromes, Magics, and Possessional Acts. (2nd July 2016) - Butler, Beverley
Abstract : In this paper I present critical insights into the efficacies of heritage. I take the phenomenon of the Jerusalem Syndrome (JS) as my point of departure and recast it as Heritage Syndrome (HS). I do this to better understand how such efficacies are experienced and materialized in ritual possessional acts. As a framework, the JS reveals the power and potency that reside in experiences of collapse. Such disembedding events activate subsequent ritual dramas (whether malign/benign or successful/failed) of world-making, redemption, repair, and renewal. Heritage quests as ritual 'sacred dramas' and 'practical magics' are I argue, similarly experienced in the collapse of known categories: imagined/real, extraordinary/mundane, possessing/being possessed, and crucially what heritage is versus what heritage does . Writ large, heritage efficacies are bound-up in the breakdown and blurring of boundaries — and thus the non-distinction — between heritage in the conventional sense and other dynamics such as magic, prophecy, and well-being/ill-being. These reveal alternative pathways, potentialities, and patterns of behaviour that demonstrate that dominant, elite, rationalized approaches to heritage banalize heritage efficacies and can thus be termed a failed project. I argue that conceiving of heritage as a syndrome — and critically as a movement away from medical pathologization and towards a recasting of heritages as diverse constellations of cultural-spiritual-magical-emotional experiences and engagements — better reflects the deeply felt complex and transformative practices at play. These heritage rites distinguished at points by those who wish their lives were more dramatic and those who wish their lives were less traumatic better describe how the vast majority of global actors engage with heritage, notably at popular, grass-roots level and in contexts of extremis, yet its significance goes largely unrecognized and unvalued.